Symposium 9: e-Learning Groups and Communities of Practice - McConnell, David; Beer, Martin; Green, Sharon; Armitt, Gillian; Sixsmith, Andrew; van Bruggen, Johanna; Daniels, Ramon; Ghyselen, Ludo; Sandqvist, Jan; Slack, Frances; Harris, Rachel A.; Niven, Jenny; et al. (Proceedings of the International Conference on Networked Learning, 2002)
Many e-learning (or networked learning) events and courses are designed to encourage the development of groups and communities as the basis for effective learning. E-learning practitioners appear to believe that community is a key factor in the development and maintenance of quality e-learning. The purpose of this Symposium is to provide an opportunity for the presenters and participants to engage in discussion and debate on the importance - theoretically and practically - of designing e-learning events and courses which aspire to bring learners together as "community". The presentations in this Symposium engage with the idea of community from various different but related perspectives. This will become clear as each presentation unfolds. This diversity of meanings has implications for the practise of e-learning as well as the understanding of community in e-learning environments. This will be explored in the Symposium. Papers: Developing Communities of Interest in a European Internet School Martin Beer, Sharon Green, Gillian Armitt, Andrew Sixsmith, Johanna van Bruggen, Ramon Daniels, Ludo Ghyselen, Jan Sandqvist and Frances Slack Retrofitting theory to practice - a reflection on the development of an e-learning community Rachel A Harris and Jenny Niven Negotiation, identity and knowledge in e-learning communities David McConnell POLARIS: A Tool For The Support Of Interactions In Learning Communities Frans Ronteltap Exchanging Stories in Learning Circles, an Imaginative Experience Diana Shore The Potential for the Use of Computer-Mediated Communication (CMC) in Teacher Professional Development Maria Zenios, Frank Banks and Bob Moon